calcule o valor da expressão
3 ^ -1 + 2 ^ -2 - (-4) ^ -1
Soluções para a tarefa
Respondido por
1
para mudar o sinal do expoente nos invertemos o numero
![=3^{-1}+2^{-2}-(-4)^{-1} \\ \\ = \frac{1}{3}+ (\frac{1}{2})^2 -( -\frac{1}{4} ) \\ \\ \\ = \frac{1}{3}+ \frac{1}{4}+ \frac{1}{4} \\ \\ =\frac{1}{3}+ \frac{2}{4} \\ \\ = \frac{4+6}{12} \\ \\ = \frac{10}{12} \\ \\ = \frac{5}{6} =3^{-1}+2^{-2}-(-4)^{-1} \\ \\ = \frac{1}{3}+ (\frac{1}{2})^2 -( -\frac{1}{4} ) \\ \\ \\ = \frac{1}{3}+ \frac{1}{4}+ \frac{1}{4} \\ \\ =\frac{1}{3}+ \frac{2}{4} \\ \\ = \frac{4+6}{12} \\ \\ = \frac{10}{12} \\ \\ = \frac{5}{6}](https://tex.z-dn.net/?f=%3D3%5E%7B-1%7D%2B2%5E%7B-2%7D-%28-4%29%5E%7B-1%7D+%5C%5C++%5C%5C+%3D+%5Cfrac%7B1%7D%7B3%7D%2B+%28%5Cfrac%7B1%7D%7B2%7D%29%5E2++-%28+-%5Cfrac%7B1%7D%7B4%7D+%29+%5C%5C++%5C%5C++%5C%5C+%3D+%5Cfrac%7B1%7D%7B3%7D%2B+%5Cfrac%7B1%7D%7B4%7D%2B+%5Cfrac%7B1%7D%7B4%7D++++%5C%5C++%5C%5C++%3D%5Cfrac%7B1%7D%7B3%7D%2B+%5Cfrac%7B2%7D%7B4%7D+%5C%5C++%5C%5C+%3D+%5Cfrac%7B4%2B6%7D%7B12%7D++%5C%5C++%5C%5C+%3D+%5Cfrac%7B10%7D%7B12%7D+%5C%5C++%5C%5C+%3D+%5Cfrac%7B5%7D%7B6%7D++)
Respondido por
1
3 ^ -1 + 2 ^ -2 - (-4) ^ -1
1 + 1 - (-1) mmc = 12
3 4 4
4 + 3 + 3 ==> 10 ou 5
12 12 6
Perguntas interessantes
Geografia,
1 ano atrás
Artes,
1 ano atrás
Psicologia,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás